IMMUNOGENICITY AND PROTECTIVE EFFICACY OF RECOMBINANT VACCINE BASED ON THE RECEPTOR-BINDING DOMAIN OF THE PLASMODIUM VIVAX DUFFY BINDING PROTEIN IN AOTUS MONKEYS - AREVALO-HERRERA, MYRIAM; CASTELLANOS, ANGELICA; YAZDANI, SYED S; SHAKRI, AHMAD RUSHDI; CHITNIS, CHETAN E; DOMINIK, ROSALIE; HERRERA, SOCRATES (The American journal of tropical medicine and hygiene, 2005)
Invasion of human erythrocytes by Plasmodium vivax requires interaction between Duffy binding protein (PvDBP) and the Duffy blood group antigen. The receptor-binding domain of PvDBP lies in a conserved N-terminal, cysteine-rich region, region II (PvRII). PvRII is a valuable malaria subunit vaccine candidate for asexual blood stages. We have evaluated in Aotus monkeys the immunogenicity and protective efficacy of recombinant PvRII formulated in Freund’s and Montanide ISA720 adjuvants. Specific antibody titers were determined by an enzyme-linked immunosorbent assay after each of three doses of 50 μg of protein administered by the subcutaneous route. Immunization with PvRII formulated in Freund’s adjuvant yielded higher antibody titers than immunization with the Montanide ISA720 formulation and offered partial protection. Although the Montanide ISA720 formulation was immunogenic, it did not provide any protection. Given the immunogenicity and partial protection observed, further studies are needed to optimize the PvRII vaccine formulation with adjuvants suitable for human use.